Determinants of Interest Rate Spreads in Solomon Islands - Rebei, Nooman (IMF Working Papers; Working Paper ;, 2014)
Bank interest rate spreads in Solomon Islands are high by regional standards. This paper examines the determinants of bank interest rates including bank specific, banking sector, macroeconomic, and legal indicators. The results show that the scale of operation, overhead costs, concentration index, and some macroeconomic variables (i.e., monetary policy rates and real growth) significantly influence interest rate margins. The paper particularly focus on the influence of the banking sector structure and finds strong evidence of bank collusion.